A New Triterpenoid Saponin and Antimicrobial Activity of Ethanolic Extract from Sapindus mukorossi Gaertn. (8th July 2012) - Sharma, Amita; Sati, Satish Chandra; Sati, Om Prakash; Sati, Maneesha Dobhal; Kothiyal, Sudhir Kumar; Semwal, Deepak Kumar; Mehta, Anil
Abstract : A new acetylated triterpenoid saponin elucidated as hederagenin-3- O - β -D-xylopyranosyl (2→1)-[3- O -acetyl- α -L-arabinopyranosyl-28- O - α -L-rhamnopyranosylester has been isolated from pericarps of Sapindus mukorossi Gaertn. The structure of the compound was determined by means of chemical and spectral analysis including advanced 2D NMR studies. The ethanolic extract from pericarps of the plant showed significant in vitro antimicrobial activity against various test organisms by Agar well diffusion method.